2020
DOI: 10.1101/2020.12.12.20246934
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CD177, a specific marker of neutrophil activation, is a hallmark of COVID-19 severity and death

Abstract: COVID-19 SARS-CoV-2 infection exhibits wide inter-individual clinical variability, from silent infection to severe disease and death. The identification of high-risk patients is a continuing challenge in routine care. We aimed to identify factors that influence clinical worsening. We analyzed 52 cell populations, 71 analytes, and RNA-seq gene expression in the blood of severe patients from the French COVID cohort upon hospitalization (n = 61). COVID-19 patients showed severe abnormalities of 27 cell population… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 75 publications
(142 reference statements)
0
3
0
1
Order By: Relevance
“…2B). Remarkably, expression of these genes is attenuated in PMNs from the severe patients, whose neutrophils displayed increased activation markers including GBP5 (activator of NLRP3 inflammasome assembly) (27) and CD177, previously associated with COVID-19 severity and death (28), as well as stress-related genes such as IRAK3, FKBP5, IL1R2 (Fig. 2B).…”
Section: B) Neutrophils From Mild Patients Have Increased Expression Of Genes Associated Withmentioning
confidence: 87%
“…2B). Remarkably, expression of these genes is attenuated in PMNs from the severe patients, whose neutrophils displayed increased activation markers including GBP5 (activator of NLRP3 inflammasome assembly) (27) and CD177, previously associated with COVID-19 severity and death (28), as well as stress-related genes such as IRAK3, FKBP5, IL1R2 (Fig. 2B).…”
Section: B) Neutrophils From Mild Patients Have Increased Expression Of Genes Associated Withmentioning
confidence: 87%
“…Destabilizing the CD177:mPR3 complex decreases ANCA-induced neutrophil activation and autoimmune diseases [42]. Another study indicated that CD177 serves as a specific neutrophil activation marker to predict the severity and mortality of COVID-19 [43].…”
Section: Neutrophil Degranulationmentioning
confidence: 99%
“…We used and normalized the data by implementing the R 3.6.1 software package "Limma", and to explore the expression of differential genes (DEGs) in GSE171110 and GSE22098 between disease groups and the healthy controls samples, respectively (14,15). Genes with adjusted P-value less than 0.05 and |log2-fold change (log2FC)| more than 1.0 were defined as statistically DEGs.…”
Section: Differential Expression Genes Identification Between Sle And...mentioning
confidence: 99%